Spatial suitability assessment for planning infrastructure facilities at site level in hill areas - N. Kapoor; Vijay Kr. Bansal (Journal of Urban Management, 2021)
Hill areas have gained considerable attention in recent years because of continuously increasing demand for infrastructure facilities. Spatial planning of infrastructure facilities is a challenging task in hill areas because of topographical variations, ecological sensitivity, and extreme climatic conditions. This becomes more critical because of the lack of an integrated quantitative approach for the assessment of land for its suitability. The paper aims at the spatial suitability assessment for planning infrastructure facilities at site level in hill areas. This has been accomplished in four stages; identification of the criteria, determination of weights of the criteria, spatial suitability assessment of the site, and scenario generation. In the first stage, a structured literature survey was done for the identification of the criteria influencing spatial planning of infrastructure facilities in the hill areas. In the second stage, an expert questionnaire survey was conducted for determining the percentage influence of the criteria and the responses were analysed through the analytical hierarchy process. In the third stage, spatial suitability map was generated in geographic information system for locating the infrastructure facilities. The vulnerability map was created for identifying the hazard prone areas. In the fourth stage, the developed suitability map and vulnerability map were aggregated to generate the scenario. A case study was taken for the implementation of the developed methodology which is useful for decision making for practitioners involved in the planning of infrastructure facilities in hill areas.
Keywords: 710; Criteria; Expert opinion; Hill areas; Suitability analysis; Vulnerability analysis